Metaphors and Similes in The Book of Revelation - Susan Maria; Barli Bram (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The article aims to examine meanings of the figurative language, namely metaphors and similes in the Book of Revelation in the Bible. The figurative language found in the Book of Revelation is used to emphasize to the reader terms, parables, or visions about what John saw. The research used qualitative content analysis and document analysis as the method to analyze the data found. The findings showed 34 figurative languages of metaphor and simile in the revelation which are in 26 verses. The metaphor only has 4 verses, while the simile has 30 verses. Metaphors are few compared to similes because in the Book of Revelation, there are not many words of God but parables about what will happen in the future according to John's vision. The analysis of simile uses the comparison to compare animals and objects, comparing the characteristics of the human body and objects, comparing the condition or situation of humans and objects, and comparing objects, both concrete and abstract. The findings of the research would be an alternative way to learn and understand the figurative language in the Bible: Book of Revelation.